Effects of carageenan coating and chemical dip on the quality of fresh-cut green saba (Musa balbisiana) slices - Yuga, Hazel Hannah J.; Borazon, Elaine Q. (c2011.)
ABSTRACT This study aimed to evaluate the effects of carrageenan and/or chemical dip on the quality of fresh-cut green Saba (Musa balbisiana) slices. Saba slices were treated with 3-minute chemical dip and/or 1-minute carrageenan dip. Visual Quality Rating (VQR) and physicochemical properties of the slices were observed until the limit of marketability was reached. Enzyme kinetic parameters at 28°C using catechol as a substrate were determined for the most effective treatment. VQR results showed that both 2% calcium chloride + 2% citric acid and 2% calcium chloride + 2% ascorbic acid were able to retard the browning of Saba slices and extend their marketable life for 13 days on LDPE bags at 14-17°C. Both treatments were not able to maintain the moisture content and firmness of the slices throughout the observation period. However, only slices treated with 2% calcium chloride + 2% ascorbic acid showed reduced respiration rate based on minimal changes in pH, TA, and TSS. Kinetic parameters showed that both treatments were able to significantly (p<0.05) retard the enzymatic browning of the slices. However, 2% calcium chloride + 2% ascorbic acid (Km = 3.72±0.50, Vmax= 3.30±0.42, Vmax/Km=0.90±0.24) presented itself a more effective enzymatic browning inhibitor.
Thesis(B.S. Food Technology)--University of the Philippines Diliman
Keywords: Fruit -- Processing; Bananas -- Preservation